f(x)=2x+4, g(x)= 4x^2+3; Find (g.f)(3)

so when doing this start with the first part which is g*f or g.f

that means you have (2x+4)(4x^2+3) so when you foil this you multiply each term in one to each term in the other.

2x*4x^2 = 8x^3 2x*3 = 6x 4*4x^2 = 16x^2 4*3 = 12

combine any like terms, in this case there are none.

that leaves you with 8x^3 + 16x^2 + 6x + 12

next you substitute 3 in for every x

8(3)^3 + 16(3)^2 + 6(3) + 4*3 use order of operations to solve (pemdas)

8*27 +16*9 + 6*3 +4*3

216 + 144 + 18 + 12

350+ 18+ 12

368+12

380 is the answer

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up